DIGITAL TECHNOLOGIES OF FINANCIAL INSTITUTIONS: RISKS AND PROSPECTS FOR USE - Shyshkina, O. V. (The actual problems of regional economy development, 2023)
The purpose of this article is to study the main types of digital technologies, risks and prospects of their use in the activities of financial institutions. To achieve the goal, the following research methods were used: analytical – to collect, analyze and describe digital technologies for deeper understanding of a scientific problem; expert – to assess the risks and prospects of the development of digital technologies; critical analysis and comparative analysis – to compare the current and promising state of the implementation of digital technologies by financial institutions of Ukraine; the method of scientific generalization – to identify priority directions for the use of innovative digital technologies in the conditions of risk and uncertainty of the external environment. The novelty of this research lies in the analysis of the penetration of digital technologies into the activities of financial institutions, the study of possibilities of combining different types of technologies to achieve tactical and strategic goals, and the reflection of their impact on the financial sector of the national economy. Within the scientific study, it was proven that digital technologies are a key element of digital transformation, which uses them to improve the processes of financial, investment and risk management, the interaction with clients and establishing the feedback with consumers, and increasing the efficiency of their activity. It was determined that digital technologies capable of ensuring the speed, efficiency and security of financial operations have already been used in the financial sector of the national economy, such as: cloud technologies, block-chain, smart-contracts, Internet of Things, artificial intelligence, machine learning and others. It is substantiated that the use of these digital technologies enables financial institutions to analyze large volumes of data and obtain valuable information about the main trends, events and processes in the financial and other spheres, which helps the owners and managers of financial institutions make better decisions regarding investment, lending and carrying out other financial operations. The author systematized the advantages and risks of the researched digital technologies and formulated practical possibilities of their use, and determined the main prospects for their development in the short and long term. As the study showed, digital technologies have a significant potential to increase the efficiency and reduce the costs of financial institutions, and can also provide the opportunity to implement new products and services, expand the customer base and increase the profitability level of the financial institution. However, the use of these technologies requires financial institutions to invest in the development and implementation of new systems and programs, staff training and their preparing for working with such innovations.